Edukasi Gizi Pada Wanita Usia Subur - Sulymbona, Nurdewi (Universitas Negeri Gorontalo, 2024)
The nutritional status of women of childbearing age in Sinaputra Village, Cigalontang District, Tasikmalaya Regency, shows a low level of 25.5% of the total 1,227 women of childbearing age, caused by the habit of consuming an unbalanced diet. To overcome this problem, community service activities were carried out to provide an understanding of balanced nutrition through outreach using lecture and discussion methods. The results showed an increase in knowledge in 38 participants, most of whom were women of childbearing age who actively participated in the discussion. This activity reflects success in providing understanding to women of childbearing age about the importance of adequate nutritional intake to prepare themselves for pregnancy and childbirth; it is hoped that this can improve the quality of nutrition, reduce the risk of nutritional problems, and create optimal body conditions for a healthy pregnancy.